Karakteristik Koherensi Eksternal Pengenalan Pecahan pada Buku Matematika Kelas IV Sekolah Dasar - Fathma Nailal Husna; Didi Suryadi; Nadia Ulfa (Program Studi Pendidikan Matematika, FKIP Universitas Muslim Maros, 2026)
This study aims to analyze the coherence of the presentation of fraction material in the fourth-grade mathematics textbook under the Merdeka Curriculum, published by the Ministry of Education, Culture, Research, and Technology in 2022, by examining the relationships among tasks. Using a qualitative approach with content analysis, this study is grounded in an interpretive paradigm to explore phenomena in didactic design. The theoretical framework employed is the praxeology of the Anthropological Theory of the Didactic (ATD), focusing on the “type of task” component and integrated with the prospective analysis stage of Didactical Design Research (DDR). The results indicate that, although the sequence of material is structurally logical, gaps in conceptual coherence exist during transitions between tasks. The findings reveal a predominance of an empirical-visual approach in the early stages, which is not immediately followed by explicit mathematical generalizations. In addition, conceptual leaps and abrupt procedural transitions were identified, particularly in the topics of equivalent fractions, decimals, and percentages, which may trigger the emergence of didactic obstacles. This study concludes that textbook coherence needs to be strengthened through the provision of more explicit mathematical bridges to facilitate the transition from concrete understanding to formal reasoning. The findings also highlight the importance of the teacher’s role as a mediator in bridging these conceptual gaps and supporting the construction of students’ holistic understanding.